C♯ 5.0 pocket reference - Albahari, Joseph (O'Reilly, 2012)
When you need answers for programming with C♯ 5.0, this practical and tightly focused book tells you exactly what you need to know--without long introductions or bloated samples. Easy to browse, it's ideal as quick reference or as a guide to get you rapidly up to speed if you already know Java, C++, or an earlier version of C♯. Written by the authors of C♯ 5.0 in a Nutshell, this book covers the entire C♯ 5.0 language, including: All of C♯'s fundamentals Advanced topics such as operator overloading, type constraints, covariance & contravariance, iterators, nullable types, operator lifting, lambda expressions & closures LINQ, starting with sequences, lazy execution and standard query operators, and finishing with a complete reference to query expressions Dynamic binding and C♯ 5.0's new asynchronous functions Unsafe code & pointers, custom attributes, preprocessor directives, and XML documentation.